Supply Management adapted to Increase Operational Profits of MSE that Sell Massive Consumption Products in Lima, Peru - Aspilcueta Arias, Alessandra Nicole (2020)
In Peru, almost approximately 90 percent of companies are small-scale, better known as MSE (Micro and Small Enterprises), which are normally run by people with little or no management knowledge. Therefore, this research arises in order to support those small companies (MSE) that commercialize mass consumption products (“bodegas”), evaluating the relationship between their supply management and their operational profits to identify how to improve their profits and make them competitive with large companies (markets or supermarkets). The research has a quantitative approach, correlational level, descriptive method and non-experimental design, using test, questionnaires and analysis matrix as main data collection instrument. The results were obtained by evaluating a representative sample of company over a period of 3 months, analyzing on a weekly basis the Operational Profits obtained based on the application of good procurements practices. As a main conclusion, this research shows that operational profits improve when the following variables are controlled: (i) Purchasing Management (knowing how to choose suppliers), (ii) Storage (knowing how and where to store products), (iii) Inventory control (knowing the most important products, knowing when and how much to buy them, and rotating them).